Perancangan Brand Activation Melalui Instagram untuk Ready To Go - Irena, Florencia (Jurnal Vicidi, 2024)
In 2020, the world was shaken by the Covid-19 pandemic. In addition to maintaining health, the public was encouraged to continue exercising to avoid the transmission of Covid-19. One of the popular sports during the pandemic was cycling, not only because it is enjoyable but also because it can be done outdoors. The cycling trend gave rise to many cycling jersey brands to meet the high demand. One of them is Ready To Go. Therefore, in order to compete with other brands, a social media presence was created to introduce the Ready To Go brand to potential consumers. The purpose of this research is to determine the response of potential consumers on Instagram towards the Ready To Go brand. The research utilizes a quantitative method through a questionnaire distributed to 56 respondents, as well as a qualitative method involving interviews with 3 expert users, 3 extreme users, online observations of similar competitors, and a review of relevant literature and supporting journals. The findings of the study conclude that the use of Instagram as a social media platform to spread awareness to potential consumers is appropriate. Additionally, the variety of content created is appealing and aligns with current trends.